K2Pb(H2C3N3O3)4(H2O)4: a potential UV nonlinear optical material with large birefringence. Issue 14 (23rd June 2021) - Chen, Yan; Hu, Chunli; Fang, Zhi; Mao, Jianggao
Abstract : K2 Pb(H2 C3 N3 O3 )4 (H2 O)4 (I ) features a 2D [K2 PbO8 (H2 O)4 ] 12- anionic layer and reveals a moderate SHG signal of approximately 2.6 × KDP. Abstract : Cyanurate motifs are emerging functional basic blocks (FBBs) for nonlinear optical (NLO) materials and birefringent materials. Herein, we report two new potassium lead(ii ) hydroisocyanurates, namely, K2 Pb(H2 C3 N3 O3 )4 (H2 O)4 (I ) and K3 Pb(H2 C3 N3 O3 )5 (H2 O)6 (II ). I and II belong to acentric Cm and centric C 2/ m, respectively. Compound I features a novel 3D network formed by 2D [K2 PbO8 (H2 O)4 ] 12− anionic layers interconnected by (H2 C3 N3 O3 ) − anions. The 2D [K2 PbO8 (H2 O)4 ] 12− anionic layer is composed of 1D chains of edge-sharing K(1)O6 and K(2)O8 being further interconnected by 8-coordinated Pb 2+ ions. Compound II exhibits a characteristic 3D framework based on 2D [K3 PbO11 (H2 O)6 ] 17− anionic layers interlinked through (H2 C3 N3 O3 ) − groups, and the 2D [K3 PbO11 (H2 O)6 ] 17− anionic layer is based on K–O/H2 O chains bridged by Pb 2+ ions. Powder second harmonic generation (SHG) measurements of I revealed a moderate SHG response of approximately 2.6 × KDP with a type I phase-matching behavior under 1064 nm laser radiation. Theoretical calculations of I and II revealed their birefringence to be 0.325 and 0.193@532 nm, respectively. Their impressive optical properties mainly stem from stereochemically active lone pair (SCALP) Pb 2+ cations and the planar π-conjugated (H2 C3 N3 O3 ) − groups.